The measurement of destination image : the case of Austria - Pikkemaat, Birgit (Economics and Business Review, 2004)
This paper provides a short overview concerning the construct of the destination image as well as the importance of its measurement in travel context. Subsequently, the results of an empirical survey which was carried out in January 2003 with Polish students to measure the image of Austria is presented. The results particularly suggest that Austria should strengthen its cultural facilities as well as new intangible experiences, such as variety and fun or freedom and open-mindedness. (original abstract)